The Effect of Green Perceived Values and Injunctive Norms on Buying Intentions of Eco-Friendly Products - Lu'lu' Nafiati; Tri Wahyuni Sukesi; Herman Yuliansyah; Fanani Arief Ghozali; Fatwa Tentama; Bambang Sudarsono; Sulistyawati Sulistyawati; Surahma Asti Mulasari; Subardjo Subardjo (Jurnal Reksa, 2024)
This study aims to utilize the multidimensional concept of green perceived value (GPV) and injunctive norms in relation to the intention to buy environmentally friendly products. This research utilized 105 questionnaires to investigate the correlation between GPV, injunctive norms, attitudes toward purchasing, and purchase intention by focusing on four components of GPV: functional value, conditional value, social value, and emotional value. Structural equation models were employed to assess the connections among the seven components. This study adds to the existing literature by exploring the nuanced relationship between green perceived value (GPV), injunctive norms, attitudes toward purchasing, and intention to buy environmentally friendly products. By focusing on four dimensions of GPV - functional value, conditional value, social value, and emotional value - the research sheds light on how these components influence consumer behavior. Using structural equation models and analysis of 105 questionnaires, the study reveals that functional and emotional values significantly impact purchase intention via attitudes toward purchasing. These findings contribute to a deeper understanding of consumer behavior and provide insights for promoting and developing eco-friendly products. This study aims to enhance comprehension of consumer behavior and the development of intentions to buy eco-friendly products.